Impact of Service Ecology On Digital Trade Competitiveness — From Indurstrial Integration And Digital Absorptive Capacity Aspective - Tao Qu; Jiawei Li; Yongshan Chen; Zichun Li (Sekolah Tinggi Manajemen IPMI, 2023)
Based on panel data of 28 manufacturing and 6 service industries in China from 2010 to 2019, this paper uses variance partial least squares structural equation model to test the impact of service ecology on digital trade competitiveness and intermediary adjustment effect of ICT-driven manufacturing servilization at input end. Research shows producer service ecology directly promote the output and export of high-end services. Within a service ecology, when specialization level intensifies, key elements will shift from logistics and finance to finance and technology. When ICT-driven service ecology improves, it’s impact on digital trade competitiveness will change from a direct way to an indirect way. In a meshed service ecosystem, ICT driven service promote digital exports through manufacture servilization. The more developed ICT industry is, the greater this promotion forces will be. In a chained service ecology, ICT-driven manufacturing have better digital absorption capacity. So we suggest to establish digital service ecology surrounding manufacturing scene, so as to trigger manufacturing servilization at input end and enhance industrial digital absorption capacity. At the early stage of service ecology, we should first develop logistics and financial clusters. When service ecology reach certain level, we transfer to develop digital technology and finance, innovate financial products and models, and attract related elements to formulate service-ecology. We should synchronous develop ICT-driven server and manufacturing, and foster data flows cross borders, encourage leading manufacturers to open symbiotic technology platforms and transform into service-oriented enterprises.